Impact of Grant-in-Aid Projects at CSIR-National Metallurgical Laboratory, India: A Bibliometric Study - Mishra, P.N.; Goswami, N. G.; Panda, K. C. (Journal of Information and Knowledge)
The purpose of this study is to evaluate the impact of 204 Grant-in-Aid projects carried out at CSIR-National Metallurgical Laboratory, India during 1995-2010 through Bibliometric method. Unearths the impact of projects in the light of current needs to sustain in future. The data pertaining to study were generated through structured questionnaire. The output-identified as deliverables of each project includes, cash flow, process developed, patents, copyright, and technology transferred, academic contribution and research papers published through projects.The quality of papers were traced out through citation and impact factor. The Projects have been classified at different level of research-basic research, applied research, industrial research. The data further presented according to the level of research to accommodate 204 projects. The duration of the projects ranged from 6 months to 5 years. A group of 27 subject areas have been identified for all the projects, fall in the domain of Metallurgy and Materials Sciences and allied subjects.The value of projects were estimated around 55 Crore Rupees. About 97% projects were accomplished in scheduled time. The R&D output reflects that 55 processes were developed and only one technology could be transferred. However 21 technologies are under negotiation for transfer to different parties. During the tennure of projects, 40 patents and 14 copyrights were filed. About 58 students from various reputed academic institutions were benefited through projects. A total of 608 research papers were reported based on projects findings. The trends of publications during 16 years show that SCI papers are in increasing trends and reflects a healthy sign as performance indicators of the sponsored projects. The projects under basic research contributed a maximum of 226 papers with 845 citations, shared 64.50% of the total 1310 citations. The average impact factor of papers was 1.552. The highly cited papers published in the area of water quality-assessment, received 88 Citations, other highly cited papers fall in the domain of corrosion protection and prevention, waste management and utilization and materials science and technology. The output of the present work will be useful for scientists and decision makers to judge the impact of Grant-in-Aid projects in the light of current global scenario and making project selection mechanism more effective by tailoring to the current needs of the society.